PENGALAMAN PEREMPUAN DALAM BERMEDIA SOSIAL UNTUK MEMENUHI KEBUTUHAN INFORMASI KESEHATAN MENTAL PASCA PANDEMI (Studi Fenomenologi pada Pengikut Akun Instagram @wmnlyfe) - Ladya Safa Anindita (2023)
As a result of the COVID-19 pandemic, the phenomenon of mental health issues such as depression, excessive anxiety, and psychological trauma continues to increase even as we enter the post-pandemic period. Many women are also affected by mental health disorders so that information about mental health is increasingly needed. The use of social media today is very helpful for people in getting the information they need. The @wmnlyfe account on Instagram exists as an educational platform regarding mental health issues, especially for women. Through the @wmnlyfe account, the audience can get information about mental health from various perspectives. Therefore, this study aims to find out how the experiences of women following the @wmnlyfe account on Instagram in using social media to meet their information needs related to mental health in the post-pandemic period. This study uses a qualitative method with a phenomenological approach to dig deeper into individual experiences. The theory used in this study is the theory of individual differences to find out how the different conditions of each informant can produce message effects. The results of the study showed that the five informants faced mental health issues due to the covid-19 pandemic. To meet the information needs for mental health, the informants chose the @wmnlyfe account with several considerations. Besides being able to increase the informant's knowledge about mental health, the account was also able to influence the informant's mental condition well